Asociación del SNP19 del gen«calpaína 10»a diabetes mellitus tipo 2 y factores de riesgo en población peruana - Paredes, M. (2010)
Abstract Type 2 diabetes mellitus (T2DM) is genetically defined as a complex disease caused by the interaction of environment and genes, which are located in different regions from the human genome. Calpain 10 (CAPN10) is a susceptibility gene for the disease, located in 2q37.3. The allelic and haplotypic association observed of SNP's 19, 43 and 63 in Amerindian and some European populations would confirm these results. In this research, it has been postulated that SNP's 19, 43 and 63 of CAPN10 gene were associated with T2DM in Peruvian population. It has been analyzed 45 diabetic patients and 58 non-diabetic relatives. Among other risk factor for obesity, such body mass index (BMI), hypertriglyceridemia (HTG), arterial hypertension (HTA), and hypercholesterolemia (HC), it has been identified by polymerase chain reaction (PCR) SNP's 19, 43 and 63 of CAPN10. The Hardy-Weinberg test and conditional regression logistic were used to analyze the results. The results showed association of SNP19 with T2DM (x2 = 8,31; p = 0,01) and BMI, HTG, HC in Peruvian diabetic families. The main contribution of this research is having detected these associations in the diabetic Peruvian population.